Antibacterial Activity Test on Ethanol Extract of Gedi Leaf (Abelmoschus manihot L.) on the Growth of Escherichia coli and Staphylococcus aureus - Lista Yul Zamrul; Hartati Hartati; Parawansah Parawansah (Halu Oleo University, 2019)
ABSTRACTBackground: Infectious diseases are one of the major causes of death worldwide, mostly caused by bacteria. The use of less targeted antibiotics leads to resistance cases, thus encouraging the discovery of alternative medicine.In general, gedy leaves are known as animal feed but gedy leaves contain antibacterials such as flavonoids, saponins, tannins and terpenoids. Research Purpose:This study aims to determine the antibacterial activity of ethanol extract of gedy leaves on the growth of E. coli and S. aureus. Research Method: This research uses post test only control design, free variable is ethanol extract of gedi leaves and dependent variable is bacterial growth inhibition zone. Ginger leaf ethanol extract was obtained by maceration method for 3 x 24 hours. The test of antibacterial activity using the well diffusion method. Research result: The results of ethanol extract of gedi leaf with concentration of 2.5 mg/ml, 1.25 mg/ml and 0.625 mg/ml resulted in inhibition zone to E. coli growth successively; they were 11.33 mm, 8 mm and 6.3 mm. Extracts of the same concentration also showed inhibition of S. aureus growth with inhibit zone of 8 mm, 3.6 mm and 2 mm. Conclution:The conclusion of this research is the extract ethanol of gedi leaf has antibacterial activity against E. coli and S. aureus.Keywords: Antibacterial,E. coli and S. aureus , Gedi leaf (Abelmoschus manihot L.), Infection.